Noncommunicable disease mortality in the Russian Federation: from legislation to policy - Marya Levintova; Thomas Novotny (The World Health Organization, 2004)
Political, social and economic transitions that occurred as a result of the regime change in Eastern Europe and the Russian Federation from the late 1980s to the early 1990s led to a sudden increase in mortality across the region, with more than 80% of deaths being attributable to preventable causes, such as cardiovascular disease, lifestyle factors and injuries. The Russian Federation has experienced some of the most dramatic population declines in the world. Countrywide health reforms have been implemented, although they continue to ignore the impact of the epidemic of noncommunicable diseases (NCDs) in the Russian Federation. Improvements in mortality patterns in the Russian Federation are possible only with the broader engagement of organized nongovernmental groups within the civil society that is strongly supported by Federal legislation to address NCDs. We discuss the Russian Federal legislation germane to the prevention and control of NCDs in the light of the current mortality crisis and suggest possible policy responses to this crisis.